Newborn Midwifery Care For Baby Mrs. "M" With Low Birth Weight Baby at Puskesmas Wolio Baubau City - Nofitasari; Sri Ernawati; Risnawati (International Journal of Multidisciplinary Learners, 2025)
Background: Low Birth Weight Infants (LBW) are a serious health concern due to a higher risk of mortality in the first 28 days of life. According to WHO (2019), LBW is a baby with a birth weight of less than 2500 grams. LBW babies are atn high risk of stunting, decreased intellectual ability, and other health problems that threaten the quality of human resources in the future. Objective: This study aims to provide effective midwifery care for newborns with LBW at Puskesmas Wolio in 2024. Methodology: This study used Varney’s 7-step approach and SOAP to handle LBW cases at Puskesmas Wolio and direct observation of the results. Results: The management of Mrs. "M" with LBW included temperature monitoring, nutrition, routine weighing, infection prevention, and breastfeeding counseling. There were no significant obstacles during the study. The baby’s weight increased from 2300 grams to 2550 grams, with normal vital signs. Conclusion and Suggestion: Midwifery care with Varney’s 7-step approach and SOAP for baby Mrs. "M" with LBW at Puskesmas Wolio showed positive results. The problem solving process is well done, and there is no gap between theory and case. This study proves the effectiveness of midwifery care and can be a reference for other health workers.